MATHEMATICAL COMMUNICATION ABILITY AND LEARNING INTEREST (Experiment with Yunior High Student Using PQ4R Strategy) - Fatah, Jejen Abdul; Rohimat, Aang (IKIP SILIWANGI, 2018)
This study is an experiment with pre test-post test control group design having a goal to analyze the role of Preview, Question, Read, Reflect, Recite, Review (PQ4R) strategy on students’ mathematical communication ability (MCA) and leraning interest (MLI). The study involves 58 eighth grade students, a mathematical communication test, a mathematical learning interest scale. The study found, on MCA, its N Gain, and on MLI, students getting treatment with PQ4R strategy attained better grades than the grades of students taught by conventional teaching. The first group students attained at medium grade level on MCA and fairly good grade level on MLI, while the second group students obtained at low grade level on MCA, medium grade level on MLI, and they realized few difficulties in some items of mathematical communication tasks. The other findings, there was no association between MCA and MLI